Multi-pattern Matching Methods Based on Numerical Computation - Lu Jun; Zhang Zhuo; Mo Juan; Lv Xingfeng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Multi-pattern matching methods based on numerical computation are advanced in this paper. Firstly it advanced the multiple patterns matching algorithm based on added information. In the process of accumulating of information, the select method of byte-accumulate operation will affect the collision odds , which means that the methods or bytes involved in the different matching steps should have greater differences as much as possible. In addition, it can use balanced binary tree to manage index to reduce the average searching times, and use the characteristics of a given pattern set by setting the collision field to eliminate collision further. In order to reduce the collision odds in the initial step, the information splicing method is advanced, which has greater value space than added information method, thus greatly reducing the initial collision odds. Multiple patterns matching methods based on numerical computation fits for large multi-pattern matching. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2232